Study of public policies and organization of school health services in seven West African countries - (:unkn) unknown (My University, 2023)
Our study aims to better understand how health promotion services for students are organized in West Africa (Senegal, Mali, Côte d’Ivoire, Burkina Faso, Benin, Togo, Guinea). It is based on an analysis of school health policies and the organization of these services, where they exist, as well as on interviews with health and education professionals. The school health services available are very similar in all countries, although the way they are run may vary from one country to another. Two types of organization of school health services were identified.
Keywords: African Research